تدبير الخصية المختفية دراسة استقبالية في مشفى الأسد الجامعي في اللاذقية بين عامي 2004 – 2006 - رسلان خضر; مهنا إسحاق; حاتم همام (Latakia University Journal -Medical Sciences Series, 2019)
أجريت الدراسة في مشفى الأسد الجامعي في اللاذقية في قسم الجراحة ما بين عامي 2004-2006 على 39 مريضاً, لديهم 52 خصية غير نازلة تراوحت أعمارهم ما بين ( 1 - 15 ) سنة, وكانت تهدف الدراسة إلى: 1. حساب العمر الوسطي الذي تم فيه العلاج ومعرفة التأخيرعن العمر المثالي للتدبير الجراحي. 2. معرفة نتائج ومضاعفات العمل الجراحي والعلاج الهرموني. 3 . استقصاء وجود تشوهات في السبيل البولي العلوي. . 4إمكانية التشخيص المبكر والعلاج الباكر للخصى المختفية (الهاجرة). أجري تصوير البطن بالأمواج فوق الصوتية لثلاثين مريضاً ( 76.9%) للتفتيش عن التشوهات في السبيل البولي وكانت سلبية. كان العمر الوسطي للمرضى 5. 6سنوات ، وعدد المرضى الذين أجري لهم العمل الجراحي قبل عمر السنتين 4 مرضى (25.10%). وجد غياب الخصية في حالة واحدة (1,92%), وضمور خصوي في ست حالات ( 53.11 %) من مجموع الخصى المختفية, وتم استئصال الخصية في حالتين( 3.85%). أجري إنزال الخصية وتثبيتها لـ 48 خصية, وتمت متابعة المرضى خلال شهر إلى ستة أشهر, ووجد أنّ هنالك نكساً في حالتين ( 4.16%).أما نتائج العلاج الهرموني فكانت غير موثوقة ومخيبة للآمال. The study was carried out in Al-Assad University Hospital, Lattakia, in Surgery Department for a period of two years (2004 – 2006). There were 39 patients with 52 undescended testises. Their age ranged between (1-15) years .The objects of this study were as follows: 1- To calculate the mean age, when the patients were treated, and then find the delay from the ideal age of surgical management. 2- To find the outcome of the surgery and hormonal therapy and their complications. 3- To evaluate abnormalities of urinary tract. 4- The possibility of early diagnosis, and then the early management. Ultrasound (US) was done to 30 patients (76.9%) to find the abnormalities of urinary tract, and the results were negative. The mean age was 6.5. There were 4 patients (10.25 %) who were less than 2 years old. It was found that 6 (11,53%) of total testises were atrophic and 1 ( 1,92%) vanished. Two testises (3.85%) were excised. Orchidopexy was done in the remaining cases (48 testes). These patients were followed up in a period of one month to six months, and it was found that there was a recurrence in 2 cases ( 4.16%). The outcome of hormonal therapy was unreliable and it was disappointing.